On Impulsive Lotka–Volterra Systems with Diffusion - Struk, O. O.; Tkachenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study a two-dimensional Lotka–Volterra system with diffusion and impulse action at fixed moments of time. We establish conditions for the permanence of the system. In the case where the coefficients of the system are periodic in t and independent of the space variable x, we obtain conditions for the existence and uniqueness of periodic solutions of the system.